Synthesis and characterization of vanadium disulfide nanosheets and carbonized iron cations adsorbed onto polyaniline for high-performance supercapacitor applications - Manyala, Ncholu I. (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2017.